Comparison of the effects of dexmedetomidine and remifentanil on perioperative hemodynamics and recovery profile of patients undergoing laryngeal microsurgery: A prospective randomized double-blinded study. Issue 34 (27th August 2021) - Kim, Young Sung; Chang, Hae Wone; Kim, Heezoo; Park, Jong Sun; Won, Young Ju
Abstract: Background: Laryngeal microsurgery (LMS) causes hemodynamic instability and postoperative agitation, cough, pain, nausea, and vomiting. Moreover, because of a short operation time, it is associated with challenging anesthetic management. The aim of this study was to compare the usefulness of continuous administration of dexmedetomidine and remifentanil in inducing general anesthesia in patients undergoing LMS. Methods: This is a prospective randomized control design. Continuous intravenous infusion of dexmedetomidine (group D) or remifentanil (group R) was administered from 10 minutes before the induction of anesthesia to the end of surgery. In both groups, 1.5 mg/kg propofol and 0.5 mg/kg rocuronium were administered for the induction of anesthesia, and desflurane were titrated during the measurement of the bispectral index. We recorded hemodynamic data, recovery time, grade of cough, pain score, and analgesic requirements during the perioperative period. Results: 61 patients were finally analyzed (30 for group D, 31 for group R). The incidence of moderate to severe postoperative sore throat was higher in group R than in group D (42% vs 10%, P  = .008), and the quantity of rescue fentanyl used in post-anesthesia care unit was significantly higher in group R than in group D (23.2 ± 24.7 mg vs 3.3 ± 8.6 mg; P  < .001); however, the time required for eye opening was significantly longer in group D than in group R (599.4 ± 177.9 seconds vs 493.5 ± 103.6 seconds; P  = .006). The proportion of patients with no cough or single cough during extubation was comparable between the 2 groups (group D vs group R: 73% vs 70%) as was the incidence of hemodynamic instability. Conclusion: Although there was a transient delay in emergence time, dexmedetomidine reduced postoperative opioid use and the incidence of sore throat. Dexmedetomidine may be used as an alternative agent to opioids in patients undergoing LMS.